PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP PEMAHAMAN KONSEP SISWA KELAS V SDN CIKOKOL 4 KOTA TANGERANG - Erika Puspita Dewi; Septy Nurfadhillah; Rizki Zuliani (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
This research aims to determine the effect of the discovery learning model on the conceptual understanding of class V students at SDN Cikokol 4, Tangerang City. This research is research that uses a quantitative approach with the Quasi Experimental method. The population in this study was 87 class V students at SDN Cikokol 4 Tangerang City with a sample of 57 students divided into 30 class V A students and 27 class V B students. Data collection techniques consisted of observation sheets, test instruments and documentation. The test instruments (pretest and posttest) used are 15 essay questions each. This research was tested and analyzed using EXCEL. In the results of the posttest hypothesis test using the pooled variance model t-test formula, tcount was 7.24 and ttable was 2.00. Because tcount > ttable, it can be concluded that H0 is rejected and H1 is accepted, which means that there is an influence of the discovery learning model on understanding the concepts of science subjects. The average posttest score in the experimental class was 80.1 and 75.25 in the control class posttest class. This can show that the use of the Discovery Learning learning model increases students' understanding of science subject concepts more significantly